Cloning and characterization of cDNAs for murine macrophage inflammatory protein 2 and its human homologues (The Rockefeller University Press, 1990)
A cDNA clone of murine macrophage inflammatory protein 2 (MIP-2) has been isolated from a library prepared from lipopolysaccharide (LPS)- stimulated RAW 264.7 cells and the nucleotide sequence determined. This cDNA was used to clone cDNAs for human homologues of MIP-2 from a library prepared from phorbol myristate acetate-treated and LPS- stimulated U937 cells. Two homologues were isolated and sequenced. Human MIP-2 alpha and MIP-2 beta are highly homologous to each other and to a previously isolated gene, human gro/melanoma growth- stimulating activity (MGSA). These three human genes, MIP-2 alpha, MIP- 2 beta, and gro/MGSA, constitute a sub-family within the cytokine family represented by platelet factor 4 and interleukin 8.